2020
DOI: 10.1371/journal.pone.0243843
|View full text |Cite
|
Sign up to set email alerts
|

Developing a national birth cohort for child health research using a hospital admissions database in England: The impact of changes to data collection practices

Abstract: Background National birth cohorts derived from administrative health databases constitute unique resources for child health research due to whole country coverage, ongoing follow-up and linkage to other data sources. In England, a national birth cohort can be developed using Hospital Episode Statistics (HES), an administrative database covering details of all publicly funded hospital activity, including 97% of births, with longitudinal follow-up via linkage to hospital and mortality records. We present methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…However, birth cohorts derived from HES data have been extensively validated and widely used for research of birth outcomes. [28][29][30][31] Further, we demonstrated that the distribution of recorded gestational age among births identified in HTI was representative of births in England, and the distribution of risk factors among eligible infants with and without any missing data were comparable. Linkage of HES to NHS Birth Notification database (maintained by NHS Digital) could provide complete information on key birth characteristics for all births.…”
Section: Strengths and Limitationsmentioning
confidence: 67%
See 1 more Smart Citation
“…However, birth cohorts derived from HES data have been extensively validated and widely used for research of birth outcomes. [28][29][30][31] Further, we demonstrated that the distribution of recorded gestational age among births identified in HTI was representative of births in England, and the distribution of risk factors among eligible infants with and without any missing data were comparable. Linkage of HES to NHS Birth Notification database (maintained by NHS Digital) could provide complete information on key birth characteristics for all births.…”
Section: Strengths and Limitationsmentioning
confidence: 67%
“…Missing data rates were comparable to these reported in wholecountry birth cohorts derived from HES. 28,29 Completeness and accuracy of gestational age is known to vary between hospitals (as submission of these variables to HES is not mandatory), with some hospitals reporting no recorded data, and some reporting invalid data which were removed when preparing the cohort. 29 We could not use multiple imputation to take missing data into account in our models, since multiple imputation requires all analyses to be run on the same sample size.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…HES contains details of all admissions to National Health Service (NHS)-funded hospitals and captures 97% of births in England 15. Maternal and infant birth admissions contain information about maternal and infant characteristics, while subsequent infant hospital admissions enable longitudinal follow-up 15 16. Diagnoses and procedures in HES are recorded using the International Classification of Diseases 10th revision (ICD-10) and the Classification of Surgical Operations and Procedures, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…By linking data we gain a less fragmented view of individual interaction with, or pathways through services and the courts (Jay et al 2017). In addition, there is a wealth of excellent literature on approaches to data linkage (Harron et al 2017, Zylbersztejn et al 2020). In the discipline of health in particular, there are multiple examples of robust studies that have linked data across organisational sources to build holistic analyses of patients' engagement with health services and their outcomes (Harron et al 2020).…”
Section: Joining Up the Dots: Record Linkage For Justice Researchmentioning
confidence: 99%